PENGARUH SOSIALISASI PERPAJAKAN, PELAYANAN FISKUS DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA SEMARANG BARAT DAN KPP PRATAMA SEMARANG TIMUR - Annisa Fattika, 12.05.52.0190; Srimindarti, Ceacilia (Students' Journal of Accounting and Banking, 2016)
Taxes have the bigges important role as a source of revenue and income for the country for improved welfare of the people. One of the biggest taxpayer requested for accountinng, deposit, and reporting tax payable is the individual taxpayer. The biggest problem that always appears in a community is the influence of non-compliance / complience of individual Taxpayers or agencies fo pay taxes obligations becouse of low knowledge, and not yet started comprehensive. This study examines the effect of socialization tax, service tax authorities, and tax penalties for individual taxpayer compliance. This study exsamines is Performance in KPP Pratama Semarang Barat and KPP Pratama Semarang Timur. Data used in this study, the primary data. Sources of primary data in this study obtained directly from randomly selected individual taxpayer in KPP Pratama Semarang Barat dan KPP Pratama Semarang Timur as many as 100 samples. By using multiple linear regression techniques. This results showed that taxations socialization, service tax authorities, and tax penalties positive and significant impact on the individual taxpayer compliance in Semarang.  Keywords: Taxation Socialization, Service Tax Authorities, Tax Penalties